A chemical stable 1D Cd(II) di-phosphonic acid coordination polymer with district luminescent property. (1st January 2019) - Xu, Hailong; Feng, Lu; Wang, Qiaoyun; Huang, Wentao; Zhou, Hong
Graphical abstract: A new cadmium phosphonate has been synthesized and the properties of thermal, water stability and luminescent have been investigated. Abstract: A new metal phosphonate, [Cd(H2 L)H2 O]n (1 ), (H4 L = 4-F-C6 H4 CH2 N(CH2 PO3 H2 )2 ) has been synthesized by hydrothermal method and structurally characterized by X-ray single-crystal diffraction, infrared spectroscopy, elemental analysis and powder X-ray diffraction.1 exhibits a 1D chain structure formed by the coordination interactions between PO3 groups and metal ions. The adjacent chains are further interlinked by hydrogen bond interactions, leading to a supramolecular network. Moreover, 1 not only shows excellent stability in boiling water, DMF solution and 140 °C hydrothermal condition for three days, but also can survive in aqueous solution over a wide pH range. To the best of our knowledge, this is the first report of diphosphonic acid complex with 1D chain exhibiting high stability in various solutions. The thermal stability was also investigated. Additionally, the luminescence property of1 was investigated in the solid state at room temperature.